Antibiotic Utilization Patterns at Sidorejo Kidul Community Health Center, Salatiga City in April 2025 - Saffra Tahtania Pramaesti; Ndari Asiyah; Hesti Prasetiyaningrum; Anifatul Maula; Anita Kumala Hati (Universitas Ngudi Waluyo, 2025)
Inappropriate antibiotic use remains a serious public health problem, contributing to increasing rates of bacterial resistance, including multidrug resistance. Although the government has issued official guidelines through Minister of Health Regulation No. 28 of 2021, approximately 60% of Indonesians do not use antibiotics rationally (Yunivita et al., 2024). This study aims to determine the pattern of antibiotic use among outpatients at the Sidorejo Kidul Community Health Center during April 2025. The population in this study was all outpatients receiving antibiotics, with a sample consisting of total patient data that met the criteria. The variables studied included the name of the antibiotic, dosage form, dosage strength, dosage instructions, number of doses administered, and diagnosis or indication for antibiotic use. This study is a descriptive quantitative study with retrospective data collection, namely analysis using a data collection method based on antibiotic use data among patients at the Sidorejo Kidul Community Health Center. Based on the results of the study, it was found that the use of antibiotics was more in female patients than in male patients, namely 60.9%, then for the age group that received the most antibiotics was > 41 years with a percentage of 39.9%, the most widely used antibiotic group was the penicillin group, especially amoxicillin, followed by the fluoroquinolone and cephaloporin groups, the most widely used dosage form was tablets. Thus, it can be concluded that the Pattern of Antibiotic Use at the Sidorejo Kidul Community Health Center is dominated by amoxicillin in tablet form in adult patients and is in accordance with the reference and diagnosis of the disease.